A comparison of ignition characteristics of slurry fuels prepared using coal processing waste and finely divided coal. Issue 4 (August 2019) - Vershinina, K.Yu.; Shlegel, N.E.; Strizhak, P.A.
Abstract: The scientific novelty of the research is that for the first time differences in the conditions and characteristics of the ignition and burning of droplets of slurries prepared on the basis of coals and waste from their enrichment have been established. The practical significance of the research results is that they illustrate the prospects of utilization of the numerous coal enrichment wastes by combustion in the composition of aqueous slurries with the generation of a rather large amount of energy and a relatively small negative environmental impact. The most significant characteristics were compared: the limiting (minimum) temperature; the ignition delay times; the maximum combustion temperature; the concentration of the main gas anthropogenic emissions. It has been found that fuel mixtures prepared from wet waste of coal flotation are characterized by higher inertia and ignition temperatures compared to slurries with high-quality coal dust. However, the established differences considering the availability and low cost of filter cakes illustrate the prospects of waste derived fuel combustion. The combustion heat of the investigated slurries based on coal and filter cake with addition of petroleum products differs by no more than 5–30%. The average difference between the duration of ignition for fuel droplets based on dust and filter cake of coking and low-caking coals is about 20%. At that the addition of waste turbine oil (10% wt.) into the filter cake reduces the duration of ignition by 12–25% and the ignition temperature – by 10–15 °C without a significant increase in anthropogenic gas emissions. The difference between the minimum ignition temperatures of coal and waste coal based slurries was from 10 °C to 80 °C. On environmental and economic indicators, coal waste is more attractive than coal. Graphical abstract: Image 1 Highlights: Coal processing waste can be effectively disposed by burning within the slurry fuels. Ignition delay times of slurry increase on average by 20% if coal waste is used. Threshold ignition temperatures of slurry change by 10–80 °C if coal waste is used. Combustion temperatures of slurries change by 40–80 °C if coal waste is used. According to relative indicators, it is advisable to use coal waste in the slurries.